The importance of Reaction Time in Athletics: Influence on the Results of Sprint Runs of World Championships Finalists - Pavlovic, R. (Central European Journal of Sport Sciences and Medicine, 2021)
In athletic sprint disciplines, the segments of start and start acceleration occupy an important place that significantly generates the final outcome of the race. The question is to what extent the start time of the reaction (latent time) has a contribution to achieving the results of sprint disciplines. The aim of the current research was to determine the influence and connection between the reaction time and the result performance of running in the disciplines of 100 m, 200 m, 400 m finalists of ten world championships. The results of a total of 456 finalists (231 men) and 225 (women) competitors who competed in the final races of the championships (from Edmonton, 2001 to Doha, 2019) were analyzed. The evaluation of the start reaction time and sprint results was based on reports officially published by the International Association of Athletics Federation (IAAF). Central and dispersion parameters were calculated for all variables. The relationship between reaction time and sprint results was calculated using the Pearson correlation coefficient, and simple regression analysis determined the direct influence of reaction time on the result success and calculated the relevant coefficients for the level of statistical significance p < 0.05. Based on the obtained results, a positive but low correlation was recorded between the mean values of the 100 m sprint results and the reaction time in men (r = 0.230p < 0.044), which was also confirmed by regression analysis. In other correlations and values of regression coefficients, no significant numerical values of the influence of reaction time on the result success were recorded in both categories of finalists.